Examining the Relationship between Middle School Students' Critical Reading Skills, Science Literacy Skills and Attitudes: A Structural Equation Modeling - Ersin Karademir; Ufuk Uluçınar (Seyit Ahmet Kıray, 2017)
The purpose of this study is to verify the causal relationship between middle school students' critical reading skills, science literacy skills and attitudes towards science literacy with research data according to the default model. Through the structural equation modeling, path analysis has been applied in the study which was designed in correlational model. The sample of the study consists of 1170 students enrolled in 18 schools determined based on socio-economic status. However, the results showed that validity criteria was satisfied with the 1130 participants. As data collection tool, the scale of critical reading skills, science literacy skills test, and the attitude scale toward science literacy were used. Descriptive statistics, Pearson product moment correlation analysis technique and path analysis were employed for the data analysis. The findings of the research show that there are significant and positive relations between critical reading skills, science literacy skills and attitudes towards science. In addition, critical reading skills have a statistically positive predictive effect on science literacy skill. It has also been founded that science literacy skills predict the attitudes towards scientific literacy in a meaningful way. Moreover, critical reading skills directly predict the scientific literacy in a meaningful, positive direction. It has been revealed that science literacy skill, which exists in the model, acts as partial mediating variable. As a result, as put forward in theory, critical thinking, critical reading skill, and science literacy skills and attitudes have been found to be closely related.